Estimasi Index Kematangan Berbagai Varietas Pisang Berbasis Spectroscopy - Eka Bellia Wulandari (Fakultas Teknologi Pertanian, 2025)
Bananas are one of the high-value fruit commodities, in nutrition and economic. As a climacteric fruit, bananas undergo a rapid ripening process, especially when stimulated by calcium carbide. The research was conducted from February to March 2025 at the Laboratory of Precision Agriculture and Geoinformatics, University of Jember. The samples were taken from three banana varieties (Susu, Barlin, and Ambon) in Jember Regency. In this study, a non destructive spectroscopy method was used to analyze the ripeness levels of various banana types, both natural ripened and carbide ripened. The analysis results showed that the spectrometer could estimate the ripeness of bananas based on reflectance from six samples (Susu, Barlin, and Ambon, both natural and with carbide). Each banana variety displayed different ripening characteristics, with a green color at 500-550 nm (due to chlorophyll) and brownish-black at 781-800 nm (indicating decay), where the reflectance curve for spoiled bananas is flatter compared to the green ones.
Reaploud Repository Mei 2026 :: Finalisasi Repositori File 11 Juni 2026_Kurnadi
Keywords: banana varieties; ripeness; spectrometer.